Cyclic Mappings and Further Results in B-Metric-Like Spaces - Shengquan Weng; Quanxin Zhu; Baoying Du; Kaibo Shi (Complexity)
Fixed point problem of many mappings has been widely studied in the research work of fixed point theory. The generalized metric space is one of the research objects of fixed point theory. B-metric-like space is one of the generalized metric spaces; in fact, the research work in B-metric-like spaces is attractive. The intention of this paper is to introduce the concept of other cyclic mappings, named as Lβ-type cyclic mappings in the setting of B-metric-like space, study the existence and uniqueness of fixed point problem of Lβ-type cyclic mapping, and obtain some new results in B-metric-like spaces. Furthermore, the main results in this paper are illustrated by a concrete example. The work of this paper extend and promote the previous results in B-metric-like spaces.